Geoelectrical Resistivity Profiling Surveys as a Guide for Geotechnical Pile Capacity Design Calculations: A Case Study - Taher T.M.; Omar R.C.; Wahab W.A.; Roslan R.; Solemon B.; Rafek A.G.M.; Jaapar A.R.; Isa A.A.M. (Springer Science and Business Media Deutschland GmbH, 2024)
Developing critical infrastructure in quaternary marine deposits requires detailed preliminary information to design a construction plan. The preferred approach for soil physical and mechanical properties determination is testing and analyzing soil samples obtained through drilling and subsurface investigations. Resistivity profiling surveys are commonly related to the energy industry. Thus, this study used resistivity profiling to establish an initial relationship using geoelectrical resistivity values with a standard penetration test, SPT-N value. Based on the profile, a low resistivity value ranging between 25.5 and 15.8 ?.m and thickness from 3.0m to 9.2 m signifies a saturated zone. Electrical resistivity showed a significant correlation with soil properties as the finding recorded low resistivity in soft sandy clay with an N value lower than 7, while firmer soil has an N value greater than 7. The findings are also applied to obtain parameters that can estimate early design, especially in determining geotechnical pile capacity. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.